Human Papillomavirus Type Distribution and Correlation with Cyto-Histological Patterns in Women from the South of Italy - Paola Menegazzi; Luisa Barzon; Giorgio Palù; Elisa Reho; Luigi Tagliaferro (Hindawi Limited, 2009)
Human papillomavirus (HPV) type-specific distribution was evaluated in genital samples collected from 654 women from the South of Italy undergoing voluntary screening and correlated with cyto-histological abnormalities. HPV DNA was detected in 45.9% of the samples, 41.7% of which had multiple infection and 89.0% had high-risk HPV infection. The prevalence of HPV infection and the rate of multiple infections decreased with age, suggesting natural selection of HPV types with better fitness. In line with other Italian studies, the most common HPV types were HPV-6 and HPV-16, followed by HPV-51, HPV-31, HPV-53, and HPV-66, in women with both normal and abnormal cytology. Cervical intraepithelial lesions grade 2 or 3 were associated with high-risk HPV-16, HPV-18, HPV-31, and HPV-51 infection. These data indicate that prophylactic HPV vaccination is expected to reduce the burden of HPV-related cervical lesions in this population, but also suggest the potential utility of new vaccines with larger type coverage.